2023
DOI: 10.1186/s13568-023-01530-1
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of an anti-cancerous cytokine: human IL-29 gene in Chlamydomonas reinhardtii

Abstract: Green algae, Chlamydomonas reinhardtii, with low cultivation cost, absence of endotoxins and insusceptibility to human pathogens is emerging as a potential system for the future production of recombinant proteins. The recent development of molecular tools enabling recombinant protein expression in algae chloroplast has provided new research and advance opportunities for developing low-cost therapeutic proteins. In the present study, algae chloroplast expression system was evaluated for the recombinant producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…The yield in current study was higher (98 mg/l) in comparison to other studies who have reported as 60 mg/l (Li & He 2006 ), 65 mg/l (Xie et al 2007 ), and 70 mg/l (Shaldzhyan et al 2021 ). The antiproliferation activity of rhIL-29 in HepG2, HCT-116, and MCF-7 cell lines was consistent with previous reports (Fujie et al 2011 ; Balabanov et al 2019 ; Akram et al 2023 ; Rahman et al 2023 ), indicating that our research is successful in producing functional IL-29.…”
Section: Discussionsupporting
confidence: 92%
“…The yield in current study was higher (98 mg/l) in comparison to other studies who have reported as 60 mg/l (Li & He 2006 ), 65 mg/l (Xie et al 2007 ), and 70 mg/l (Shaldzhyan et al 2021 ). The antiproliferation activity of rhIL-29 in HepG2, HCT-116, and MCF-7 cell lines was consistent with previous reports (Fujie et al 2011 ; Balabanov et al 2019 ; Akram et al 2023 ; Rahman et al 2023 ), indicating that our research is successful in producing functional IL-29.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the deleted plastome region was designed to extend as far as a well-established neutral locus for transgene insertion, ensuring that psbH restoration was always accompanied by transgene insertion. TN72 has been used by several groups to create marker-free transgenic lines producing recombinant therapeutics [ 14 , 15 , 16 , 17 , 18 , 19 ]. However, TN72 has several drawbacks as a platform strain.…”
Section: Introductionmentioning
confidence: 99%
“…Microalgae stands as a promising biological platform for the cost‐effective and sustainable production of recombinant proteins and bioproducts using only water, CO 2, and sunlight. The microalgae C. reinhardtii is one of the most studied algae species and has been developed as a potent and photosynthetic expression system for the production of recombinant proteins, antigens, fatty acids, and chemicals with wide industrial applications [21–24] . In addition, C. reinhardtii can be grown autotrophically, heterotrophically, or even mixotrophically using various carbon sources [25] .…”
Section: Introductionmentioning
confidence: 99%
“…The microalgae C. reinhardtii is one of the most studied algae species and has been developed as a potent and photosynthetic expression system for the production of recombinant proteins, antigens, fatty acids, and chemicals with wide industrial applications. [21][22][23][24] In addition, C. reinhardtii can be grown autotrophically, heterotrophically, or even mixotrophically using various carbon sources. [25] Well-documented molecular tools serving the efficient and high-level expression of transgenes in nuclear and chloroplast genomes have also been developed, making microalgae suitable hosts for synthetic biology and biotechnology.…”
Section: Introductionmentioning
confidence: 99%